Integrated GWAS and transcriptomic analysis reveal the candidate salt-responding genes regulating Na+/K+ balance in barley (Hordeum vulgare L.) - Xu, Tingting; Meng, Shan; Zhu, Xiaopin; Di, Jiachun; Zhu, Yin; Yang, Xin; Yan, Wei (Frontiers in Plant Science, 2023)
Salt stress is one of the main abiotic stresses affecting crop yield and quality. Barley has strong salt tolerance, however, the underlying genetic basis is not fully clear, especially in the seedling stage. This study examined the ionic changes in barley core germplasms under the control and salt conditions. Genome-wide association study (GWAS) analysis revealed 54 significant SNPs from a pool of 25,342 SNPs distributed in 7 chromosomes (Chr) of the Illumina Barley 50K SNP array. These SNPs are associated with ion homeostasis traits, sodium (Na+) and potassium (K+) content, and Na+/K+ ratio representing five genomic regions on Chr 2, 4, 5, 6, and 7 in the leaves of worldwide barley accessions. And there are 3 SNP peaks located on the Chr 4, 6, and 7, which could be the “hot spots” regions for mining and identifying candidate genes for salt tolerance. Furthermore, 616 unique candidate genes were screened surrounding the significant SNPs, which are associated with transport proteins, protein kinases, binding proteins, and other proteins of unknown function. Meanwhile, transcriptomic analysis (RNA-Seq) was carried out to compare the salt-tolerant (CM72) and salt-sensitive (Gairdner) genotypes subjected to salt stress. And there was a greater accumulation of differentially expressed genes(DEGs) in Gairdner compared to CM72, mainly enriched in metabolic pathway, biosynthesis of secondary metabolites, photosynthesis, signal transduction,emphasizing the different transcriptional response in both genotypes following salt exposure. Combined GWAS and RNA-Seq analysis revealed 5 promising salt-responding genes (PGK2, BASS3, SINAT2, AQP, and SYT3) from the hot spot regions, which were verified between the salt-tolerant and salt-sensitive varieties by qRT-PCR. In all, these results provide candidate SNPs and genes responsible for salinity responding in barley, and a new idea for studying such genetic basis in similar crops.